A Comprehensive Study on Applications of Blockchain in Wireless Sensor Networks for Security Purposes - Mui Duc Nguyen; Minh Tuan Nguyen; Thang Chien Vu; Tien Minh Ta; Quang Anh Tran; Dung The Nguyen (Journal of Computing Theories and Applications, 2024)
The paper evaluates potential applications of blockchain technology in enhancing the security and reliability of Wireless Sensor Networks (WSNs). The existing vulnerabilities in WSNs, such as concerns regarding data integrity and security, demand innovative security solutions. Through systematic analysis, this paper provides valuable insights to expand understanding of WSNs security, explaining the feasibility and benefits of deploying blockchain technology. Possible attacks in the networks are classified to point out either risks or potential solusions to protect the networks. By exploring the integration of Blockchain within WSNs, the paper highlights its potential to minimize various security risks. In addition, this work discusses the challenges and considerations associated with implementing Blockchain in WSNs. Overall, this paper contributes on securing WSNs and underscores the role of blockchain technology as a promising way for enhancing security of WSNs.